Pelatihan dan Pendampingan English for Tour Guide Pada Program Pendidikan Kecakapan Kerja 2021 di Kabupaten Situbondo - Dwi Taurina Mila Wardhani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2021)
The Employment Skills Education Program (PKK) is a government assistance program that aims to prepare human resources who are skilled, have character, are competitive, and have the ability to innovate. This is an aid to industry-based courses and training and entrepreneurial opportunities. Through the results of initial observations that have been made, graduated students of English Literature Faculty of Letters UNARS do not have special courses on skills as a tour guide. Through the English for Tour Guide Training program those who are interested in following the skills as a tour guide are included as participants in the 2021 PKK program and will be trained to have competence as a tour guide. PKM program participants who gain the skills to become tour guides will be very useful as their provision to find work. In collaboration with the AUSEI course institution as a service partner for PKM activities, it is hoped that later PKK program participants will have a competency certificate to work. This training and mentoring are carried out for approximately three months where students are given English language guidance and training that focuses on the English for Tour Guide material. During the training, students also had the opportunity to discuss and ask questions if they encountered problems during the training to reach the right solution. The expected outcome of this PKM activity is that students have special skills in English about English for Guides as evidenced by a certificate of competence. Keywords: English, English for Tour Guide, PKK program.